The payoff time: a flexible framework to help clinicians decide when patients with comorbid disease are not likely to benefit from practice guidelines. - Braithwaite, R Scott; Fiellin, David; Justice, Amy C (Medical care, 2009)
Practice guidelines rarely consider comorbid illness, and resulting overuse of health services may increase costs without conferring benefit.
Keywords: Aged; Chronic Disease; Colorectal Neoplasms; Comorbidity; Cost-Benefit Analysis; Decision Making; Female; Frail Elderly; Guideline Adherence; Health Care Rationing; Humans; Male; Mass Screening; Middle Aged; Practice Guidelines as Topic